Advancing a Holistic Framework for Classifying SAI Performance Audit Impact Factors: Integrated Scientific Assumptions - Šaliene, Asta (Buhalterinės apskaitos teorija ir praktika, 2024)
The article raises the problem of the need to reconceptualize the framework of the impact factors of the performance audit performed by Supreme Audit Institutions (SAI). The research aims to identify performance audit impact factors and propose an expanded, comprehensive framework. To implement the aim, the integrative method of scientific literature analysis is employed. Throughout the study, a systematic exploration of scientific literature is conducted to identify and organize hypothetical and previously researched impact factors discussed by scholars. The identified factors are aggregated according to their characteristics, meaning, or nature, and are divided into ten pillars: accountability, context, legitimacy, political overtones, quality of the performance audit, social relations, stakeholders, logic of public administration, the multifunctional activity of performance audit, and the individual. The broader framework of performance audit impact factors created will be beneficial for further research into managing these factors, enhancing evaluation opportunities, enabling performance auditors to mitigate associated risks, and capitalizing on the positive properties of these factors.
Keywords: SAI audit; performance audit; impact of performance audit; impact factors of performance audit